Social representation about Indians in Sergipe: absence and invisibility - Lima, Marcus Eugênio Oliveira; Almeida, Alan Magno Matos de (Paidéia (Ribeirão Preto), 2010)
Aiming to understand the social representations of people in Sergipe, Brazil about Indians, 378 residents of six cities were interviewed (five cities in Sergipe and one in Alagoas). The results revealed the predominance of a social representation of Indians whose main meaning is formed by elements that refer to a past or remote time or which denote physical and cultural distance (i.e. "woods", "forests", "nudity", painting" etc). In a similar way, when participants were asked about what they recalled of Indians in the Brazilian history, they seldom mentioned recent events and had difficulty to mention even remote facts. Living far away from an Indian tribe had less impact on social representations than what was expected. The conclusion is that for many participants, Indians exist only as an absence or yet in naturalized way, as phenotypic and cultural remnants of a 500-year history of violence and extermination.